PEMBENTUKAN KARAKTER GEMAR MEMBACA PADA ANAK USIA DINI MELALUI MEDIA BUKU CERITA BERGAMBAR - Fitriatul Masruroh; Eka Ramiati (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This article aims to explain the importance of maintaining character education, especially for early childhood to cultivate a sense of reading through the media of picture storybooks. This article uses the Literature study method by examining library data such as books, magazines, documents, historical stories, or related research objects. The formation of characters like to read children is very important because to prepare children to face the elementary school level. Early childhood growth and development is very rapid. Then the ability to read in children needs to be considered. By reading children will gain new information, knowledge and experiences. Remembering the childhood is a true adventure and learning that is full of honesty in realizing his thoughts and expressing his feelings. All parents certainly want to make their children happy, seeing them grow up healthy, intelligent, and successful in their lives actively in moving so that children are healthy both physically and spiritually.